2015
DOI: 10.1002/ejic.201500617
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Oxidation Synthesis of Modafinil Acid by Use of a Recyclable Chiral‐at‐Metal Complex

Abstract: The enantioselective oxidation synthesis of chiral modafinil acid and its analogues with high enantiomeric excess has been developed by means of a chiral‐at‐metal strategy. Treatment of ruthenium complexes cis‐[Ru(bpy)2Cl2] or Δ/Λ‐[Ru(bpy)2(MeCN)2](PF6)2 (bpy is 2,2′‐bipyridine) with the appropriate prochiral thioether ligands afforded thioether complexes rac‐1, Δ/Λ‐1, rac‐2, Δ/Λ‐2, rac‐3, and Δ/Λ‐3. Diastereoselective oxidation of the thioether complexes in situ produced the corresponding sulfoxide complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The N1 and N2 atoms are at trans position with the angle of N1–Ir1–N2 = 170.4(2)°; this is consistent with its parent. The Ir1–S1 distance of 2.357(1) Å is in accord with the reported distance for the Ir­(III) sulfoxide complexes. , The S–O bond distance of 1.499(3) Å is consistent with that reported in sulfoxide complexes. , A pair of enantiomers Δ- R and Λ- S are found in the crystal structure; thus, the complex is racemate. Two pairs of diastereomers Δ- R and Δ- S , and Λ- R and Λ- S , would be generated when rac - trans ( N )-[(Ir­(ppy) 2 Cl) 2 ] reacted with rac -HLO- i Pr in the experimental conditions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The N1 and N2 atoms are at trans position with the angle of N1–Ir1–N2 = 170.4(2)°; this is consistent with its parent. The Ir1–S1 distance of 2.357(1) Å is in accord with the reported distance for the Ir­(III) sulfoxide complexes. , The S–O bond distance of 1.499(3) Å is consistent with that reported in sulfoxide complexes. , A pair of enantiomers Δ- R and Λ- S are found in the crystal structure; thus, the complex is racemate. Two pairs of diastereomers Δ- R and Δ- S , and Λ- R and Λ- S , would be generated when rac - trans ( N )-[(Ir­(ppy) 2 Cl) 2 ] reacted with rac -HLO- i Pr in the experimental conditions.…”
Section: Resultssupporting
confidence: 88%
“…That is, the Δ Ir­(III)-centered configuration favors the R configuration sulfoxide while the Λ configuration center prefers the S configuration sulfoxide, leading to enantioselective recognition between the metal center receptors and chiral sulfoxides. These are consistent with the previous observations in Ru­(II) sulfoxide complexes by Meggers’ group and our group. ,, To understand this selectivity, a density functional theory (DFT) calculation was carried out for Ru­(II) and LO- i Pr complexes by Meggers’ group, and they found that the Λ- S enantiomer is more stable than the Δ- S enantiomer . As shown in Figure , the O2 of the sulfoxide group is hydrogen bonded to the C22–H of the pyridine ring (C22···O2 = 3.197 Å, H22···O2 = 2.338 Å, ∠C22–H–O2 = 153.6°); the i Pr group is far from the α-H of the pyridine ring to relieve the steric congestion and forms C–H···π interaction (2.92 Å) with the ppy ligand to stabilize the diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…Although many methodologies have been developed for preparation of chiral sulfoxides ,, and Andersen’s method is often employed to generate enantiopure sulfoxides, they still suffer from a lack of generality; the experimental procedures were tedious, and an organometallic reagent need to be used. The aerobic photo-oxidation protocol for sulfide is quantitative, chemoselective, and functional-group tolerant.…”
Section: Resultsmentioning
confidence: 99%
“…In pioneering work, Fontecave reported that Λ- and Δ-[Ru­(2,9-dimethyl-1,10-phen­anthroline)­(MeCN) 2 ] 2+ catalyze the oxidation of organic sulfides to their sulfoxides, albeit with a maximum of just 18% ee . Much higher enantio­selectivities for the synthesis of sulfoxides were achieved by Ye using chiral-at-metal Λ- and Δ-[Ru­(2,2′-bipyridine) 2 ­(pyridine) 2 ] 2+ as recyclable chiral auxiliaries . Hartung and Grubbs reported a chiral-at-ruthenium catalyst for diastereo- and enantio­selective ring-opening/cross-metathesis.…”
mentioning
confidence: 80%